2005
DOI: 10.1002/cne.20638
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen regulation of cell proliferation and distribution of estrogen receptor‐α in the brains of adult female prairie and meadow voles

Abstract: Adult female prairie (Microtus ochrogaster) and meadow (M. pennsylvanicus) voles were compared to examine neural cell proliferation and the effects of estrogen manipulation on cell proliferation in the amygdala, ventromedial hypothalamus (VMH), and dentate gyrus of the hippocampus (DG). Unlike prior studies, our study focused on the amygdala and VMH, because they are involved in social behaviors and may underlie behavioral differences between the species. Meadow voles had a higher density of cells labeled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 113 publications
1
78
1
1
Order By: Relevance
“…Smith et al (2001) observed an increase in SVZ and OB proliferation in oestrus prairie voles exposed to a male behind a mesh fence. In line with the presence of estrogen receptors in the SVZ (Fowler et al, 2005), this socially-induced surge in proliferation was not observed in ovariectomized females, and was rescued by estradiol treatment. Interestingly, estradiol administration in isolation does not exert an effect on SVZ proliferation (Hnatczuk et al, 1994).…”
Section: Gonadal Control Of Adult Neurogenesismentioning
confidence: 59%
“…Smith et al (2001) observed an increase in SVZ and OB proliferation in oestrus prairie voles exposed to a male behind a mesh fence. In line with the presence of estrogen receptors in the SVZ (Fowler et al, 2005), this socially-induced surge in proliferation was not observed in ovariectomized females, and was rescued by estradiol treatment. Interestingly, estradiol administration in isolation does not exert an effect on SVZ proliferation (Hnatczuk et al, 1994).…”
Section: Gonadal Control Of Adult Neurogenesismentioning
confidence: 59%
“…The amygdala, which is a potential site for estrogen modulation of feeding behavior (Geary, 2001), is sensitive to circulating steroids (e.g. Jasnow et al, 2006), shows steroiddependent neurogenesis (Fowler et al, 2005), and develops novel neuronal connections during adolescence (e.g. Cunningham et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in gonadal hormones associated with these interactions also may contribute to these alterations in neurogenesis [8,9, reviewed in 11]. In addition to established proliferative zones (DG and SVZ) cell proliferation in the amygdala is responsive to alterations of social environment and hormonal treatments in prairie voles [8,9,10]. Based upon the existence of proliferation in this nucleus and its well established role in social behaviors, including parental behaviors, we performed measurements within select subdivisions (medial and central nuclei) of the amygdala in addition to the DG and SVZ.…”
Section: Adult Neurogenesis Occurs In Several Mammalian Species [Revimentioning
confidence: 99%